1993
DOI: 10.1161/01.cir.87.3.963
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock response and limitation of tissue necrosis during occlusion/reperfusion in rabbit hearts.

Abstract: Our findings demonstrate a considerable increase in expression of HSP71 in myocardium from hyperthermia-treated rabbits. Infarct size was significantly reduced after 30 minutes of CO and 3 hours of Rep in hearts at 24 but not 40 hours after heat shock compared with control hearts. We conclude that heat shock-induced cardioprotection is transient and delays the onset of irreversible myocardial injury caused by ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(123 citation statements)
references
References 34 publications
6
115
0
2
Order By: Relevance
“…They showed a strong relationship between the acquisition and decay of the postischemic ventricular recovery of the heart and the induction of HSP70. 30 In contrast, Currie et al 31 demonstrated that in spite of easily detectable expression of HSP70, hyperthermia-induced myocardial protection was observed only transiently at 24 hours and dissipated by 40 hours. These studies show that the protective effect of stress preconditioning does not always correlate with HSP70 induction.…”
Section: Resultsmentioning
confidence: 96%
“…They showed a strong relationship between the acquisition and decay of the postischemic ventricular recovery of the heart and the induction of HSP70. 30 In contrast, Currie et al 31 demonstrated that in spite of easily detectable expression of HSP70, hyperthermia-induced myocardial protection was observed only transiently at 24 hours and dissipated by 40 hours. These studies show that the protective effect of stress preconditioning does not always correlate with HSP70 induction.…”
Section: Resultsmentioning
confidence: 96%
“…For example, transgenic overexpression of HSP70 in the myocardium confers protection against both myocar- dial stunning and infarction following ischemia (14,21,28,30,42), whereas pharmacological induction of HSP70 in the myocardium also imparts resistance to ischemia (15,20,29,46). Furthermore, heat stress induction of HSP70 in the myocardium is associated with the development of "cross tolerance" to subsequent prolonged ischemia (4,43). Thus numerous studies substantiate the conclusion that cellular expression of HSP70 can confer protection against I/R injury in the myocardium.…”
Section: Discussionmentioning
confidence: 96%
“…Although IP of the myocardium has been shown to increase the expression of inducible HSP70 in the myocardium and is associated with cardioprotection (4,16,22,27,44), no direct evidence has been reported to support the conclusion that HSP70 mediates the late cardioprotection induced by IP. Moreover, two previous studies suggest that expression of inducible HSP70 following IP does not provide protection against ischemia, as assessed by a reduction in infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…More than 10 differentially expressed genes were found in total 588 genes, most of these were digestive enzyme related genes, one of the overexpression gene was inducible heat shock protein 70 gene [20] . A variety of chemicals, viruses, and noxious stimuli such as trauma, hypoxia, or ischemia trigger the heat shock response and the subsequent synthesis of heat shock proteins [35][36][37][38][39][40][41][42][43] . The results of our experiment indicated that sleep deprivation as a stress resulted in significantly greater expression of inducible heat shock protein 70 in gastric mucosa of rats, which was confirmed by RT-PCR, Western blotting and immunostaining.…”
Section: Discussionmentioning
confidence: 99%